Romeo and Juliet - Shakespeare, William (London : Collins Classics, 2011)
Romeo and Juliet was the first drama in English to confer full tragic dignity on the agonies of youthful love. The lyricism that enshrines their death-marked devotion has made the lovers legendary in every language that possesses a literature.
Includes index.
Keywords: Romeo (Fictitious character) -- Drama; Conflict of generations -- Drama